2020
DOI: 10.3390/pathogens9060416
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Amino-Terminal Domain of the ISAV Fusion Protein with a Cognate Cell Receptor

Abstract: The infectious salmon anemia virus (ISAV), etiological agent of the disease by the same name, causes major losses to the salmon industry. Classified as a member of the Orthomyxoviridae family, ISAV is characterized by the presence of two surface glycoproteins termed hemagglutinin esterase (HE) and fusion protein (F), both of them directly involved in the initial interaction of the virus with the target cell. HE mediates receptor binding and destruction, while F promotes the fusion process of the viral and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Immunophilins such as FKBP5 have been previously reported to participate in viral replication during some infections such as HIV-1 [ 31 ]. Regarding serine protease 23, ISAV possesses a fusion glycoprotein (F) and an hemagglutinin esterase (HE), both necessary for viral attachment and internalization into salmon cells [ 32 , 33 ]. Influenza A has to be cleaved for the virus to enter the cell, and that is done by a serine protease secreted by the host cell [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunophilins such as FKBP5 have been previously reported to participate in viral replication during some infections such as HIV-1 [ 31 ]. Regarding serine protease 23, ISAV possesses a fusion glycoprotein (F) and an hemagglutinin esterase (HE), both necessary for viral attachment and internalization into salmon cells [ 32 , 33 ]. Influenza A has to be cleaved for the virus to enter the cell, and that is done by a serine protease secreted by the host cell [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that co-expression of HE with deleted HPRs promotes the activity of the F protein, probably because full-length HPRs hide the cleavage site of the fusion protein, impeding its activation [ 18 ]. Additionally, a recent study described that the amino-termini of the fusion protein (F1) can interact with a cellular membrane receptor and modulates HE-mediated adsorption [ 19 ], suggesting that the HPR region is closely related to the activity of the F protein. However, the basis and implications of this interaction remain unknown.…”
Section: Introductionmentioning
confidence: 99%